logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
0 votes

What does $cos^{-1} \frac {4}{5} +cos^{-1} \frac{12}{13}$ reduce to?

Can you answer this question?
 
 

1 Answer

0 votes
Toolbox:
  • \( cos^{-1}x+cos^{-1}y=cos^{-1} (xy- \sqrt{1-x^2} \sqrt{1-y^2} )\)
Given $cos^{-1} \frac {4}{5} +cos^{-1} \frac{12}{13}$
We know that \( cos^{-1}x+cos^{-1}y=cos^{-1} (xy- \sqrt{1-x^2} \sqrt{1-y^2} )\)
By taking \(x=\frac{4}{5}\:and\:y=\frac{12}{13}\:in\:the\:above\:formula,\:we\:get\)
\(cos^{-1}\frac{4}{5}+cos^{-1}\frac{12}{13}=\) \( cos^{-1} \bigg[ \frac{4}{5}.\frac{12}{13}-\sqrt{1-\frac{16}{25}} \sqrt{1-\frac{144}{169}} \bigg]\)
\(= cos^{-1} \bigg[ \frac{48}{65}-\frac{3}{5}.\frac{5}{13} \bigg]=\:cos^{-1}\big(\frac{48}{65}-\frac{15}{65}\big)\)
\( =cos^{-1} \frac{33}{65}\)
answered Mar 14, 2013 by balaji.thirumalai
 
Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...